Prescribers Adherence to the Basic Principles of Prescription Order Writing in Shashemene Referral Hospital and Malka Oda District Hospital (Annals of Medical Research, 2021)
None
Keywords: Prescribers; Adherence; Prescription Order Writing; Hospital Pharmacies; Ethiopia.